Beyond traditional testing: enhancing mathematical e-learning with stack and Step-by-Step assessment - Igor Orlovskyi; Olena Tymoshenko (ЗУІ ім. Ференца Ракоці ІІ, 2025)
Abstract. Modern mathematics education faces significant challenges, which require innovative approaches aligned with STEM principles. Research indicates that STEM students often struggle with mathematical concepts essential to their fields, such as complex numbers in electrical engineering or elementary functions in biology. These difficulties arise from procedural thinking, insufficient practice, and the inability to apply mathematical reasoning to real-world scenarios. Distance learning remains a vital component of education. However, traditional tests cannot fully assess students’ problem-solving processes. A more interactive digital environment is essential to support conceptual understanding and skill development. Igor Sikorsky Kyiv Polytechnic Institute utilizes the Sikorsky distance learning platform, based on Moodle, to enhance distance learning. As a widely used learning management system, Moodle allows course customization, test development, and detailed tracking of student progress. Studies show that Moodle-based learning improves student performance and engagement. To improve mathematical assessment, the Department of Mathematical Analysis and Probability Theory introduced Step-by-Step tests. Unlike traditional assessments that focus solely on final answers, these structured tests evaluate the key steps in problem-solving.
Keywords: mathematics education; STEM students; Step-by-Step tests